The impact of severe lung disease on evidential breath analysis collection. Issue 4 (July 2016) - Seccombe, Leigh M.; Rogers, Peter G.; Buddle, Lachlan; Karet, Barbara; Cossa, Gavina; Peters, Matthew J.; Veitch, Elizabeth M.
Abstract: Background: It is a legal requirement to supply a breath analysis sample when requested by Police at roadside checkpoints. The current device requires a 1 L sample at 8 L·min − 1 . Court disputes commonly attribute respiratory disease for failure to produce a sample. Objective: To determine whether respiratory disease aetiology and/or severity precludes an adequate breath sample using a modern evidential breath analyser. Methods: Subjects performed breath analysis following standard Police procedure. Three efforts within 15 min were allowed and any reasons for failure recorded. Results: 24 subjects with interstitial lung disease (ILD) and 26 subjects with chronic obstructive pulmonary disease (COPD) were studied and met minimum respiratory function criteria as per device specifications. 18 ILD subjects (75%) and 24 COPD subjects (92%) were able to provide a sample. All subjects with a vital capacity below 1.5 L were unable to provide a sample. Discussion: In the balance of probabilities most patients with lung disease are able to supply an evidential breath sample. The exception is a very severe disease, particularly in volume limited patients. Highlights: A failure to supply an evidential breath sample may be attributed to lung disease. Moderate to severe lung disease patients' predominately met sample requirements. The exception is very severe disease, particularly with volume limitation. The law enforcement officer may improve compliance with enhanced instruction.